Thermomagnetic and structural analysis of as‐quenched Ni49Co1Mn37Sn13. Issue 5 (31st March 2014) - Louidi, S.; Suñol, J. J.; Bachaga, T.; González‐Legarreta, L.; Rosa, W. O.; Hernando, B.
Abstract: It is known that Co substitution in magnetic shape memory Ni‐Mn‐Sn alloys produces changes in their thermomagnetic behaviour. In this work, the Ni49 Co1  Mn37 Sn13 alloy was obtained by melt spinning in ribbon shape. The ribbon flakes were characterized by scanning electron microscopy (SEM), X‐ray diffraction (XRD), vibrating sample magnetometry (VSM) and differential scanning calorimetry (DSC). SEM micrographs indicate the formation of textured ribbons with columnar grains growing up perpendicular to the ribbons plane. The crystallographic structure of the sample at room temperature is the Heusler L21 . DSC cyclic scans reveal the martensitic transformation on cooling and the reverse austenitic transformation on heating below room temperature. The application of a magnetic field produces a decrease in the transformation temperatures. The small amount of Co addition increases the Curie temperature of austenite. These facts suggest that the structural and magnetic phase transformation temperatures of the ribbons could be tuned to the desired functional temperature by controlling the applied magnetic field as well as the cobalt amount. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)